Troubled Times, Changing Tides: A Seroprevalence Study on Meningococcal Immunity in France Between 2016 and 2024 - Samy Taha; Aude Terrade; Oumar Doucoure; Ala-Eddine Deghmane; Muhamed-Kheir Taha (Vaccines)
Background/Objectives: In France, non-pharmaceutical interventions (NPIs) implemented to control COVID-19 led to a significant decline in invasive meningococcal disease (IMD) cases. However, a rebound in cases, particularly for serogroups W and Y, was observed after the gradual lifting of NPIs, raising questions about an “immunity gap” due to reduced circulation of the bacteria. During the study period, vaccination against MenC was mandatory from 2018, and vaccination against MenB has been recommended since 2022. Methods: We conducted a retrospective seroepidemiological study using 166 normal sera collected between 2016 and 2024. Anti-Neisseria meningitidis IgG levels were quantified by ELISA using purified capsular polysaccharides for serogroups B, C, W, Y, and X. Samples were categorized into three periods: pre-NPIs (n = 72), during NPIs (n = 33), and post-NPIs (n = 61). Statistical comparisons were performed using Kruskal–Wallis tests for non-parametric data. Results: Our results show a significant decline in anti-serogroup B IgG antibody levels after the lifting of NPIs (p < 0.0001) in line with reduced circulation. Anti-serogroup C IgG antibody levels increased incrementally (p = 0.0003), particularly in those aged 1–4 years, likely reflecting a catch-up in anti-meningococcal C vaccination coverage. Anti-serogroup W IgG antibody levels remained stable, suggesting sustained circulation, but shifted to young children in the post-NPI period, potentially due to a genotypic shift. Anti-serogroup Y IgG antibody levels transiently increased significantly (p < 0.0001) during the NPI period but then decreased back after their lifting. Anti-serogroup X IgG antibody levels remained stable, consistent with its low prevalence and the absence of targeted vaccination.